1992
DOI: 10.1577/1548-8667(1992)004<0007:mdibba>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Deformities in Brown Bullheads Administered Dietary β-Naphthoflavone

Abstract: Brown bullheads Ameiurus nebulosus were exposed for 28 d to chemically contaminated sediments from tributaries of the Great Lakes. The fish were subsequently transferred to sediment-free water and fed a diet containing 500 mg #-naphthoflavone/kg for 90 d in an effort to promote neoplasms. Following the #-naphthoflavone treatment, the fish were given untreated feed for an additional 150 d. The fish had no abnormalities after exposure to sediment for 28 d and no neoplasms after 268 d. However, fish fed 0-naphtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Implicit in this hypothesis is the concept that if the concentrations of a PAH AhR ligand are maintained at appropriately high levels within an organism then toxic effects similar to that produced by TCDD should be observed. Consistent with this hypothesis, a recent study reported that juvenile catfish continually exposed for 90 days to high dietary levels of β-naphthoflavone, a prototypical PAH AhR ligand, exhibited a variety of morphological and toxicological effects similar to those produced by exposure to TCDD (Grady 1992). Although significant advances in the field over the past 10 years have clearly defined the role of AhR in the toxic and biological effects of HAHs and PAHs, the exact biochemical events which lead to the spectrum of species-and tissue-specific toxic responses to these chemicals still remain to be elucidated.…”
Section: Toxicological Actions Of the Ah Receptormentioning
confidence: 88%
“…Implicit in this hypothesis is the concept that if the concentrations of a PAH AhR ligand are maintained at appropriately high levels within an organism then toxic effects similar to that produced by TCDD should be observed. Consistent with this hypothesis, a recent study reported that juvenile catfish continually exposed for 90 days to high dietary levels of β-naphthoflavone, a prototypical PAH AhR ligand, exhibited a variety of morphological and toxicological effects similar to those produced by exposure to TCDD (Grady 1992). Although significant advances in the field over the past 10 years have clearly defined the role of AhR in the toxic and biological effects of HAHs and PAHs, the exact biochemical events which lead to the spectrum of species-and tissue-specific toxic responses to these chemicals still remain to be elucidated.…”
Section: Toxicological Actions Of the Ah Receptormentioning
confidence: 88%
“…Actually, occurrence of morphological abnormalities, particularly the skeletal anomalies affecting to the opercula complex, neurocranium or vertebral column, still have a negative economical significance in the production of many marine fish juveniles. Some factors have been associated to the incidence of skeletal anomalies regardless the species affected such as mechanical damage along development, anomalous inflation of the swim bladder (Chatain and Dewavrin, 1989), tank hydrodynamic (Kihara et al., 2002), increase in culture intensiveness (Divanach et al., 1996; Sfakianakis et al., 2004; Roo et al., 2005), parasites infection (Lom et al., 1991) or presence of pesticides (Chun et al., 1981; Thi Hong Lien et al., 1997), herbicides (Koyama, 1996), hydrocarbons (Grady et al., 1992), organic and organoclorade compounds (Lindesjöö et al., 1994) and metals (Slominska and Jezierska, 2000). However, the effect of other factors such as environmental, including light, temperature or salinity (Battaglene and Talbot, 1990; Sfakianakis et al., 2004) or nutritional ones, such as dietary vitamins (specially A and C), fatty acids or aminoacids (predominantly tryptophan) (Walton et al., 1984; Akiyama et al., 1985; Takeuchi et al., 1998; Cahu et al., 1999) will vary depending on the particular characteristics of each species, and for this reason minimizing the incidence of deformities requires a deep knowledge of the specific requirements of each fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Hawkins et al, 1990;Metcalfe et al, 1988); however, very few laboratory exposure studies have investigated the link between PAH exposure and hepatic neoplasms in brown bullhead. Grady et al (1992) attempted to establish a link by exposing juvenile brown bullhead, length b 30 mm, to contaminated sediment from tributaries of the Great Lakes for 28 days. The fish were then transferred to sediment-free water and fed a diet containing β-napthoflavone, a synthetic PAH, for 90 days to promote neoplasms.…”
Section: Extrinsic Factorsmentioning
confidence: 99%